The Effect of Brazilin from Caesalpinia sappan on Cell Cycle and Modulation and Cell Senescence in T47D cells - Riris Jenie; Sri Handayani; Ratna Asmah Susidarti; Edy Meiyanto (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
Ethanolic extract and brazilein-containing fraction of Caesalpinia sappan L., has been reported to inhibit cell proliferation in T47D (ER+ PR+/- cell, Luminal A subtype model). The Luminal A subtype is the most common subtype of breast cancer in Indonesian women. In this study, we explored the activity of the reduced form of brazilein, i.e. brazilin, in T47D cells proliferation and the mechanism that involved. The cytotoxicity activity of brazilin was observed using MTT assay. While the cell cycle modulation analysis was done by using flowcytometry, and the senescence assay was observed using S-A-β-galactosidase assay. The results showed that brazilin inhibited cell growth in a dose-dependent manner with an IC50 value of 50μM (or 14.3μg/mL). That was higher than a brazilein-containing fraction, which was reported previously by our group to have an IC50 value of 68μg/mL against the same cell. Cell cycle analysis showed that cells treated with brazilin were accumulated at the G2/M phase in a dose-dependent manner. Furthermore, cells treated with a combination of brazilin and doxorubicin was accumulated at the G2/M phase and sub G1 phase. Cells accumulation at sub G1 phase indicates that the cells undergo apoptosis. Our data of S-A-β-galactosidase assay showed that cells treated with 1/4IC50, 1/2IC50, and IC50 brazilin had lower senescent cells compared to the untreated cells. The morphology of cells treated with IC50 (50μM) brazilin changed. The cells shape became rounded, cells were shrinkage and detached from the well plate, indicating that cells may undergo apoptosis. These results suggested that brazilin was cytotoxic towards T47D cells and its combination with dox potentially induced apoptosis and decreased cell senescence. The ability of brazilin to decrease cell senescence provides new insight of utilization of C. sappan or its constituents, particularly brazilin, as anti-ageing.